Experimental and numerical determination of interlayer shear strength of glass fiber-reinforced epoxy composites - Albayrak, Mustafa; Aşan, Ahmet Murat; Kaman, Mete Onur; Bozkurt, İlyas (My University, 2022)
This study aims to produce glass fiber composite plates by vacuum infusion method and to determine the interlaminar shear strength (ILSS) under the short beam test. For this purpose, composite plates were produced under the effect of vacuum and temperature by adding glass fiber layers on a flat vacuum table. Short beam tests were carried out on the obtained laminated composite plates and the interlayer shear strength, which is generally characterized by delamination damage, was investigated. In the numerical part, the tests were modeled using the LS-DYNA finite element package program, and the Hashin damage criterion-based material model was used to see the damages that occurred in the composite structure after the tests.
Keywords: LS-DYNA; Glass fiber composites; Progressive failure analysis; Short beam test